The effectiveness of rituximab and HIV on the survival of Ontario patients with diffuse large B‐cell lymphoma. (13th August 2020) - Habbous, Steven; Guo, Helen; Beca, Jaclyn; Dai, Wei Fang; Isaranuwatchai, Wanrudee; Cheung, Matthew; Chan, Kelvin K. W.
Abstract: Introduction: For patients with diffuse large B‐cell lymphoma (DLBCL), standard‐care is rituximab administered with CHOP or CHOP‐like chemotherapy (R‐CHOP). However, the effectiveness and safety of R‐CHOP among DLBCL patients with human immunodeficiency virus (HIV) infection is less clear, as HIV+ patients were omitted from most clinical trials and population‐level data from unselected patients are limited. R‐CHOP was funded for HIV‐associated DLBCL patients with CD4 >50/mm 3 in Ontario in February 2015. Methods: Patients with a new diagnosis of DLBCL were identified from the Ontario Cancer Registry between April 2010 and March 2018. HIV diagnosis and chemotherapy regimen were ascertained using administrative databases at Ontario Health. The effect of rituximab and HIV on overall survival was assessed in the HIV+ subgroup (R‐CHOP vs CHOP) and in the R‐CHOP subgroup (HIV+ vs HIV−). Results: Among HIV+ patients, receipt of R‐CHOP was associated with a fivefold improvement in overall survival (hazard ratio [HR] 0.29 (0.13‐0.66) compared with CHOP), after adjustment. Among patients who received R‐CHOP (n = 6106), older age, male sex, lower neighborhood income, and higher comorbidity were associated with worse overall survival, after adjustment ( P  < .001 for all), but HIV positivity was not prognostic (HR 1.12 (0.60‐2.10)). Within 1‐year after diagnosis, HIV+ patients receiving R‐CHOP had a similar proportion of patients who visited the emergency department (67% vs 66% P  = .43) or admitted to hospital (58% vs 52%, P  = .43) and as HIV− patients receiving R‐CHOP. Conclusion: HIV status did not affect prognosis for patients with DLBCL receiving R‐CHOP in an unselected general population when rituximab was used according to funding criteria. R‐CHOP was safe and effective for DLBCL treatment, regardless of HIV status. Abstract : The standard of care for patients with aggressive‐histology B‐cell lymphoma is rituximab in addition to a CHOP or CHOP‐like chemotherapy regimen. For HIV+ patients, there are less data available on the effectiveness of this treatment, but in 2015, policy changes in Ontario extended this treatment modality to this subgroup of patients. In the present study, we demonstrate that rituximab with CHOP is as safe and effective for HIV+ patients as it is for HIV− patients.